2003
DOI: 10.1080/1028602031000082034
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins fromPeucedanum wulongense

Abstract: A new angular dihydropyrancoumarin named wulongensin A, along with five known coumarins, (-)-anomalin, umbelliferone, (-)-smyrinol, 3'(S),4'(S)-disenecioyloxy-3',4'-dihydroseselin, (+)-trans-khellactone, was isolated from the root of Peucedanum wulongense. The structure of wulongensin A was established as 3'(R)-angeloyloxy-4'(R)-isovaleryloxy-3',4'-dihydroseselin by spectroscopic methods and the absolute configurations were deduced by chemical correlations with known compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Isolation and purification procedures of anomalin are also summarized in Table 1. As can be seen, anomalin was obtained from either aerial part and roots of the plant by extraction with petroleum ether, [36,56,57,60,68] hexane, [59,62,[64][65][66][67] diethyl ether, [70] chloroform, [51] methanol, [24,26,38,39,45 -50,52 -54,61,69,70] ethanol, [40,44,55,73,74] acetone, [41,[57][58][59] etc. at room temperature or by reflux.…”
Section: Sources and Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation and purification procedures of anomalin are also summarized in Table 1. As can be seen, anomalin was obtained from either aerial part and roots of the plant by extraction with petroleum ether, [36,56,57,60,68] hexane, [59,62,[64][65][66][67] diethyl ether, [70] chloroform, [51] methanol, [24,26,38,39,45 -50,52 -54,61,69,70] ethanol, [40,44,55,73,74] acetone, [41,[57][58][59] etc. at room temperature or by reflux.…”
Section: Sources and Isolationmentioning
confidence: 99%
“…Sheh. [51] and P. japonicum Thunb. [46][47][48] Urbagarova et al (2020) also mentioned it as (+)-praeruptorin B from Ligusticum elatum (Edgew.)…”
Section: Sources and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Peucedanum species were usually rich in essential oils and coumarins [43,44], which were basic substances for most reported pharmacological activities [45]. The yield of essential oils was various, as it could be dependent on several factors such as season [46,47], harvested stage [48] and plant part [49,50].…”
Section: Chemical Components Of the Essential Oilmentioning
confidence: 99%